Saturated Salt Solution Cadaver-Embalming Method Improves Orthopaedic Surgical Skills Training. (1st August 2018) - Burns, David M.; Bell, Ian; Katchky, Ryan; Dwyer, Tim; Toor, Jay; Whyne, Cari M.; Safir, Oleg
Abstract : Background: Human cadaver surgical skills training offers the highest-fidelity simulation of the operative environment, with the potential to enhance surgeon training and to reduce operative risks to patients. Embalming extends the duration that a cadaveric specimen may be used for surgical skills training and reduces the risk of disease transmission, but it can alter the properties of the cadaver tissue, reducing the simulation fidelity and training quality. The purpose of this controlled laboratory study was to evaluate 3 embalming methods, formaldehyde solution, alcohol-glycol solution, and saturated salt solution, and to compare their relative performance in a 2-week orthopaedic surgical skills training course. Methods: The 3 embalming methods were applied to 3 cadavers each. Joint range of motion and joint stiffness were measured prior to dissection. The cadavers were assessed by 4 orthopaedic surgeons on the first and last days of the training course in 4 domains: tissue visual fidelity, tissue tactile fidelity, odor, and overall suitability for surgical skills training using 7-point Likert scales. Sterile specimens for bacterial and fungal culture were obtained from cadaver muscle tissue on the fourth and fifteenth days of use. Results: All cadaver groups were successfully preserved without putrefaction and were utilized over the duration of the training course. The saturated salt solution cadavers had supple joints with excellent motion and were rated highly across all domains. The saturated salt solution cadaver joint motion, stiffness, visual and tactile tissue fidelity, odor, and suitability for surgical skills training were significantly superior (p < 0.05) to the formaldehyde solution and alcohol-glycol solution cadavers. Conclusions: The saturated salt embalming method is inexpensive and logistically straightforward and preserves human cadavers at room temperature in a state suitable for high-fidelity orthopaedic surgical skills training.